2011
DOI: 10.1111/j.1742-481x.2011.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus in patients with chronic wounds – are we aware?

Abstract: The incidence of tetanus in patients with wounds is unknown; however, recently concern has been raised over the proportion of tetanus cases in which a chronic wound is the portal of entry for Clostridium tetani. Varicose ulcers, dermatosis and necrosed tumours are estimated to be the point of entry for C. tetani spores in 11-14% of three cases. Of diabetic patients in the USA who contracted tetanus, a diabetic foot ulcer was responsible in 25% of cases despite this chronic wounds have yet to be considered as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…Lack of immunization is the greatest risk factor for contracting tetanus (Hsu and Groleau, 2001). With the burden of chronic wound and aging population set to increase, levels of protection amplify the risk of tetanus faced by those suffering from chronic wounds (Farnworth et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of immunization is the greatest risk factor for contracting tetanus (Hsu and Groleau, 2001). With the burden of chronic wound and aging population set to increase, levels of protection amplify the risk of tetanus faced by those suffering from chronic wounds (Farnworth et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that sufficient protection rates in DFW patients decreased with increasing age, as in the aforementioned study. Another study conducted by Farnworth et al [25] included 100 patients with chronic leg ulcer, nearly half of whom had DM. When the patients were asked about their tetanus immunization status, 48% were unsure of their status, 30% believed that they were not covered, and 22% believed that they were covered.…”
Section: Discussionmentioning
confidence: 99%
“…According to Centers for Disease Control and Prevention (CDC) data, diabetic foot ulcers and gangrene are a major route for tetanus infections. Chronic wounds, which are more commonly observed in diabetic patients, were shown to be the etiologic factor in about 26% of tetanus cases (4,8,9).…”
Section: Discussionmentioning
confidence: 99%